2020
DOI: 10.1093/eurheartj/suaa064
|View full text |Cite
|
Sign up to set email alerts
|

Causal relationship between influenza infection and risk of acute myocardial infarction: pathophysiological hypothesis and clinical implications

Abstract: Presently several evidences support an association between acute myocardial infarction and influenza infection. The pathophysiology rationale rests on the release of inflammation cytokines, rupture of atherosclerotic plaque, and triggering of prothrombotic events leading to coronary artery occlusion. Several observational evidences support a potential role of influenza vaccine in cardiovascular prevention. It is estimated that the efficacy of influenza vaccine in preventing myocardial infarction could range be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 19 publications
0
19
1
1
Order By: Relevance
“…Authors have disclosed no conflicts of interest. 3 Centre for Fertility and Health (CeFH), Norwegian Institute of Public Health, Oslo, Norway. 4 Department of Medical Quality Registries, St. Olav's University Hospital, Trondheim, Norway.…”
Section: Supplementary Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Authors have disclosed no conflicts of interest. 3 Centre for Fertility and Health (CeFH), Norwegian Institute of Public Health, Oslo, Norway. 4 Department of Medical Quality Registries, St. Olav's University Hospital, Trondheim, Norway.…”
Section: Supplementary Informationmentioning
confidence: 99%
“…Although, a vaccination might trigger coagulation abnormalities [3,4], studies showed that the benefits via preventing influenza clearly outweighs any adverse effects among individuals at high cardiovascular risk [5][6][7][8][9][10][11]. However, whether the benefits of the vaccine on cardiovascular events extend across the spectrum of cardiovascular risk are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…14 15 Third, a substantially decreased incidence of viral respiratory infections, including influenza, 16 might have decreased the incidence of AMI in these countries. 17 18…”
Section: Discussionmentioning
confidence: 99%
“…Excessive sympathetic stimulation and elevated catecholamine levels can trigger a hyperdynamic cardiovascular response, which can alter systemic and coronary vascular tone, promote vasoconstriction, and induce occlusion by preexisting atherosclerotic plaques. 79 The changes in vascular tone, the hypercoagulable state, increased platelet aggregation, and accentuated frictional or shear stress can increase the biomechanical stress present on preexisting atherosclerotic coronary artery plaques and trigger a rupture. 80 A combination of these mechanisms may explain how SARS-CoV-2 infection can unmask symptoms of coronary ischemia or aggravate preexisting predisposing factors, leading to signs of an AMI.…”
Section: Myocardial Injury and Myocarditismentioning
confidence: 99%